Estudo de assinaturas metabólicas em leiomiomas uterinos - Barison, Gustavo Anderman Silva [UNIFESP] (2022)
Objective: The present study evaluated circulating metabolites in the plasma of patients with and without leiomyomas, to define a metabolomic profile of these patients and compare them according to leiomyomas' presence and uterine size. Methods: Cross-sectional observational study, including women divided into three groups: 37 with leiomyomas and uterus over 500 cm3, 17 with leiomyomas and uterus up to 150 cm3, and 21 leiomyoma-free women. Patients underwent peripheral blood collection that was further evaluated using untargeted metabolic assessment by gas chromatography coupled to mass spectrometer. Results: There was no statistical difference between patients’ anthropometric and demographic features and general laboratory tests. Groups were statistically different for uterus volume (p<0.0001). Forty six metabolites were identified in all samples (35% were amino acids and derivatives, 22% were fatty acids and 18% were carbohydrates). Statistically significant metabolic distinction (p<0.05 and FDR<0.05) was observed for 14 metabolites. Amino acids, except for L-glutamine, were significantly reduced in plasma levels of patients with large leiomyomas. Fatty acids and carbohydrates were progressively reduced in patients with leiomyomas and even more reduced in plasma levels of patients with large leiomyomas, except for an increase in alpha- linolenic acid. Conclusion: There are differences in plasma metabolites levels of amino acids, fatty acids, and carbohydrates among patients with leiomyomas and large leiomyomas compared to leiomyoma-free patients. These metabolites are especially reduced in patients presenting large leiomyomas. This metabolic panel is an initial step for the definition of possible biomarkers and metabolic signatures of the uterine fibroid. Keywords: Leiomyoma, Metabolomics, Mass spectrometry, Lipidomics, Gas chromatography, Omic.